Development of prediction models for various distresses in jointed plain concrete pavement using machine learning and finite element modelling - Pasupunuri, Sampath Kumar (2024)
Concrete pavements deteriorate over time due to various factors, including traffic loading, climate conditions, construction quality, and initial designs. While the rate of deterioration in rigid pavements is generally slower than that of flexible pavements, the failure mechanism is more complex. Maintaining and rehabilitating concrete pavements to a serviceable condition presents a significant challenge for engineers. To devise effective maintenance strategies, a reliable pavement deterioration model is essential. This research aims to understand jointed plain concrete pavement deterioration adopting Machine Learning (ML) and numerical modelling techniques.